Alexithymia increases effects of ego-depletion - Schnabel, Konrad; Pollatos, Olga (Frontiers in Psychiatry, 2022)
Alexithymia is associated with deficiencies to identify, describe and express emotions, paucity of fantasies and an externally oriented cognitive style. The current studies provide evidence that alexithymia is also related to self-regulation processes and exacerbates effects of ego-depletion, a state where self-regulation resources are reduced due to previous acts of self-regulation. In Study 1, ego-depletion effects of a handgrip task on pain tolerance were increased by alexithymia. In Study 2, an emotion suppression task showed stronger effects of ego-depletion on a Stroop task in participants high rather than low in alexithymia, but only after suppression of emotions induced by negative and not positive pictures. Discussion focuses on the consequences of these results on the replenishment of self-regulation resources.The results imply that alexithymia increases susceptibility to ego-depletion effects, that consumption of self-regulatory resources has stronger consequences for people high in alexithymia and that they should experience special support in ways to replenish self-regulation resources.